2023
DOI: 10.1007/s10461-023-04057-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mass Media on HIV/AIDS Stigma Reduction: A Systematic Review and Meta-analysis

Abstract: HIV-related stigma is a major barrier to HIV testing and care engagement. Despite efforts to use mass media to address HIV-related stigma, their impact on reducing HIV-related stigma remains unclear. Thus, we conducted a systematic review and meta-analysis of peer-reviewed publications quantitatively examining the impact of mass media exposure on HIVrelated stigma reduction and published from January 1990 to December 2020. Of 388 articles found in the initial screening from scientific databases, 19 met the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Campaigns can be an effective way to increase HIV knowledge and awareness, particularly among socio‐economically vulnerable groups who may have limited access to health information and services [ 40 , 41 , 42 ]. Moreover, a 2023 meta‐analysis concluded that mass media campaigns can have a modest and context‐specific impact on HIV‐related stigma reduction [ 43 ]. In general terms, it is suggested that to be effective campaigns should provide accurate and up‐to‐date information about HIV transmission, prevention, testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Campaigns can be an effective way to increase HIV knowledge and awareness, particularly among socio‐economically vulnerable groups who may have limited access to health information and services [ 40 , 41 , 42 ]. Moreover, a 2023 meta‐analysis concluded that mass media campaigns can have a modest and context‐specific impact on HIV‐related stigma reduction [ 43 ]. In general terms, it is suggested that to be effective campaigns should provide accurate and up‐to‐date information about HIV transmission, prevention, testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The government has successfully utilised mass media to reduce stigma, particularly through audiovisual interventions, which have improved attitudes and behaviours towards AIDS. 59 Additionally, studies have demonstrated that health education strategies, such as zero-discrimination massive open online courses, can effectively reduce stigma among patients and caregivers. 60 External factors, such as discrimination against patients with HIV/AIDS by medical staff, also play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…The way mass media portrays these conflicts can influence public opinion. Different media outlets may frame the issues differently, emphasizing certain aspects over others [20] [21]. For example, some media sources may highlight the economic benefits of industrial development, while others may focus on the environmental consequences or conflicts with indigenous communities.…”
Section: Industry-environment Conflictsmentioning
confidence: 99%